Antimony substituted lanthanum orthoniobate proton conductor – Structure and electronic properties. Issue 11 (19th July 2020) - Mielewczyk‐Gryń, Aleksandra; Wachowski, Sebastian; Witkowska, Agnieszka; Dzierzgowski, Kacper; Skubida, Wojciech; Świerczek, Konrad; Regoutz, Anna; Payne, David J.; Hull, Stephen; Zhang, Hangfeng; Abrahams, Isaac; Gazda, Maria
Abstract: X‐ray and neutron diffraction have been utilized to analyze the crystalline and electronic structure of lanthanum orthoniobate substituted by antimony. Using X‐ray absorption spectroscopy and photoelectron spectroscopy, changes in the electronic structure of the material upon substitution have been analyzed. The structural transition temperature between fergusonite and scheelite phases for 30 mol% antimony substitution was found to be 15°C. Based on the neutron data, the oxygen nonstoichiometry was found to be relatively low. Moreover no influence on the position of the valence band maximum was observed. The influence of the protonation on the electronic structure of constituent oxides has been studied. Absorption data show that the incorporation of protonic defects into the lanthanum orthoniobate structure leads to changes in lanthanum electronic structure and a decrease in the density of unoccupied electronic states.